Determinants Influencing Small Farmers Credit Accessibility and utilization in Tanzania: A Case of Dodoma Region - Chindengwike, James (Program Studi Agribisnis bekerja sama dengan PERHEPI, 2026)
The agricultural industry employs more than 65% of Tanzanian workers and has a major economic impact. This study assesses the variables affecting small farmers' access to and utilisation of loans in Tanzania's Dodoma region. Additionally, the study uses a mixed research approach to integrate or combine qualitative and quantitative data. The research used a cross-sectional survey research methodology. The total number of grape growers in the sample was 342. For the inquiry, primary data was selected. The research discovered that Tanzanian farmers' utilization to funding is affected by bank interest rates, terms of payment, age, and education. The study recommends that development banks collaborate with the government, take the time to fully comprehend the macroeconomics of the nation in which they operate, control operating costs, and establish a stable source of income in order to successfully extend credit to underfinanced areas or sectors where other commercial banks would not.